Teacher Perceptions of Localizing ELT Material: A Study Based on the State University Sector in Sri Lanka - Siddique, F.S. (University of Jaffna, 2025)
Localization of classroom material is gaining popularity in the ELT field due to proven pedagogical benefits such as increased learner motivation and teacher enthusiasm resulting in efficient learning outcomes. For similar reasons, the concept is also applied in the Sri Lankan state university ELT units. For the effective application of localization, it is pivotal that teachers and material developers understand the concept and are efficient and knowledgeable in its execution. However, it is questionable if, in the state university system in Sri Lanka, the incorporation of localization occurs succeeding adequate teacher/learner need analysis, and a valid process of training and evaluation. The present study, therefore, aims to analyze teacher perceptions regarding localization of ELT material, strategies that teachers use, how they perceive the application of localization and the need for formal training and evaluation. The study combined both qualitative and quantitative data collection and analysis methods. Questionnaires were first collected from 53 ESL teachers representing five state universities in Sri Lanka. Next, interviews were conducted with 05 teachers selected through snowball sampling techniques. SPSS and Excel software were used to analyze the quantitative data and qualitative data were analyzed via thematic analysis techniques. The “Four Strategies for Designing Instruction for Diverse Cultures” by Orey et al. (2009) was used as the theoretical framework for understanding the strategies of localization that were revealed during the qualitative data analysis. The results showed that though theoretically, teachers perceive localization as beneficial, due to the lack of training in the application and validation in the techniques that are employed, teacher perceptions shift constantly affecting the successful application. The study, therefore, emphasizes the need for training in the localization of material and evaluation of strategies that are employed.
Keywords: Localization; Contextualization; Teacher perceptions; Localizing strategies; Teacher training and evaluation